Active commuting and physical fitness: A systematic review - Henriques-Neto D. (2020)
© 2020 by the authors. Licensee MDPI, Basel, Switzerland.Physical fitness (PF) is considered an excellent biomarker of health. One possible strategy to improve PF levels is active commuting. This review, performed accordingly to the Preferred Reporting Items for Systematic Reviews guidelines includes scientific articles published in peer-reviewed journals up to December 2019 that aim at examining the relationship between active travel/commuting and PF. The search was performed in three databases (PubMed, Scopus, and Web of Science). Sixteen studies were included in this review. Findings from the 16 studies were unclear. From the eleven studies on children and adolescents screened, eight were cross-sectional, one prospective cohort, one quasi-experimental, and one experimental. From the five studies on adults, four were experimental and one cross-sectional. Body mass, waist circumference, skinfolds, fat mass, cardiorespiratory fitness, upper and lower strength tests were performed in children, adolescents, and adults. Agility and speed tests were performed only in the young age groups. Majority of the investigations on young ages and adults have shown positive effects or relationships between active commuting and several attributes of PF. However, to avoid misconceptions, there is a need for future robust investigation to identify potential mediators or confounders in this relationship. More robust investigations are essential to understand how and whether decision-makers and public health authorities can use active travel/commuting as a strategy to improve PF in all ages.